Size-tailored polyvinylpyrrolidone–Au nanoparticles on Ni–fumarate metal-organic frameworks for dual dopamine and paracetamol sensing: a density-functional theory–assisted study - Zhou, Feng; Lim, Hong Ngee; Ibrahim, Izwaharyanie; Abdul Sisak, Muhammad Asri; Liu, Yi; Qin, Danfeng (John Wiley and Sons Inc, 2025)
Herein, the application of nickel–fumarate metal-organic frameworks (Ni-fum MOFs) adorned with gold nanoparticles (AuNPs) as a promising platform for the sensitive detection of dopamine (DA) and paracetamol (PA) in aqueous solutions is explored. The AuNPs are incorporated into the Ni–fumarate MOF composite, resulting in a novel composite biosensor, PVP–Au/Ni–fum MOF. The enhanced signal transmission capacity for DA and PA is also attributed to the strong interface between Ni–fum MOFs and AuNPs. Interestingly, this unique interface exhibits distinct catalytic properties for the redox reactions of DA and PA, thereby widening the oxidation potential discrepancy between them. The Au/Ni–fum MOF electrode displays well-resolved cyclic voltammetry peak potentials of 95.2 mV for DA and 207.5 mV for PA, with respective limit of detections of 0.0078 and 0.01 μM, respectively. In parallel, density-functional theory is employed to investigate the adsorption behavior of DA and PA on these composite materials. These results indicate enhanced adsorption energies and shorter bond lengths for the simultaneous detection of DA and PA on these composite surfaces, pointing toward the potential for dual analyte sensing. This research advances the development of advanced sensors, offering improved selectivity and sensitivity, and underscores the utility of MOFs in electrochemical sensor applications.